The Nabidae (Insecta, Hemiptera, Heteroptera) of Argentina - Cornelis, Marcela Fabiola (2013)
In Argentina, five genera and 14 species are recorded in the subfamilies Prostemmatinae and Nabinae: Hoplistoscelis sordidus Reuter, Lasiomerus constrictus Champion, Metatropiphorus alvarengai Reuter, Nabis argentinus Meyer-Dür, Nabis (Tropiconabis) capsiformis Germar, Nabis faminei Stål, Nabis paranensis Harris, Nabis punctipennis Blanchard, Nabis roripes Stål, Nabis setricus Harris, Nabis tandilensis Berg, Pagasa (Pagasa) costalis Reuter, Pagasa (Lampropagasa) fuscipennis Reuter and Pagasa (Pagasa) signatipennis Reuter.